Usaha Mikro Krupuk Singkong Desa Tempursari Kecamatan Donomulyo, Kabupaten Malang - Dyah Aruning Puspita; Marli Marli (Jurnal ABM Mengabdi, 2015)
Indonesia is an agricultural country which has a very good climate for the development of the agricultural sector, with a wide range of policies have been made by the government to promote agriculture-based economy. One of the efforts is to exploit the potential of each region, including utilizing cassava plants that are the mainstay of the village of the District Tempursari Donomulyo in Malang regency. Many things that can be produced from cassava, among others processing into chips as done by two partners in IbM program. The type crackers produced are cassava chips in the form of sticks (long slices) and crackers were given color and samiler. Demand for these products are progressively increasing the marketing area in the surrounding communities in the District Donomulyo, Gunung Kawi, Malang, Banyuwangi and many more, because this food has its own distinctive flavor and a very affordable price. Thus, the IbM program’s goal is both partners will be a pioneer for efforts raw cassava crackers another so that the economy of rural communities Tempursari District of Donomulyo will increasingly become stronger